2011
DOI: 10.1074/mcp.m111.009233
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses Reveal an Acidic Prime Side Specificity for the Astacin Metalloprotease Family Reflected by Physiological Substrates

Abstract: Astacins are secreted and membrane-bound metalloproteases with clear associations to many important pathological and physiological processes. Yet with only a few substrates described their biological roles are enigmatic. Moreover, the lack of knowledge of astacin cleavage site specificities hampers assay and drug development. Using PICS (proteomic identification of protease cleavage site specificity) and TAILS (terminal amine isotopic labeling of substrates) degradomics approaches >3000 cleavage sites were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 68 publications
(128 reference statements)
11
110
0
Order By: Relevance
“…S1 and S2) (18). The cleavage at SHCLE followed the published predicted specificities, whereas the other did not (19). The cleavage sites are located in the TIL2 and between the E2 and TIL′ domains of the MUC2 N terminus as illustrated in Fig.…”
Section: Resultssupporting
confidence: 56%
“…S1 and S2) (18). The cleavage at SHCLE followed the published predicted specificities, whereas the other did not (19). The cleavage sites are located in the TIL2 and between the E2 and TIL′ domains of the MUC2 N terminus as illustrated in Fig.…”
Section: Resultssupporting
confidence: 56%
“…The specificity of B/TP active sites differs from that of the prototypic protease astacin but is similar to that of other astacin family members in having a strong preference for aspartate in the P1Ј position of substrate cleavage sites (6,14). Crystal structure analysis has identified a basic arginine in the S1Ј pocket of BMP1, consistent with this preference for P1Ј aspartates, whereas a bulky vicinal disulfide may contribute to a restricted S1 pocket, helping to explain a preference of B/TPs for small aliphatic resides in substrate P1 positions (6,13).…”
Section: B/tp Structurementioning
confidence: 85%
“…Numerous publications have demonstrated that aggregated but soluble A␤ species have a detrimental effect on neural homeostasis and plasticity (36). For human meprin ␤, a striking preference for aspartate and glutamate residues around the cleavage site in native substrates has been revealed, demonstrating an exceptionally high specificity for a metalloprotease (22). Recently, APP was found to be a substrate of human meprin ␤, using a cell culture-based degradomic approach (15).…”
Section: Discussionmentioning
confidence: 99%
“…Using a proteomic approach, based on peptide libraries and native proteins, we discovered several new substrates, including APP, and identified a unique cleavage specificity for meprin ␤, with a preference for acidic amino acid residues (22). Here, we examined the role of meprin ␤ in overall A␤ production.…”
mentioning
confidence: 99%